Asymmetric Kulinkovich Hydroxycyclopropanation of Alkenes Mediated by Titanium(IV) TADDOLate Complexes - Iskryk, Marharyta; Barysevich, Maryia; Ošeka, Maksim; Adamson, Jasper; Kananovich, Dzmitry (Synthesis, 2019)
Asymmetric Kulinkovich cyclopropanation of carboxylic esters with prochiral alkenes is reported. The process is mediated by titanium(IV) (4R,5R)-TADDOLate complexes and affords correspondingly (Z)- or (E)-cyclopropanols with up to 84–87% ee in the event of intra- or intermolecular olefin ligand exchange in intermediate titanacyclopropane [titanium(II)-alkene] species. Configuration of the olefin double bond is preserved in the cyclopropane products, pointing out on total retention of configuration at Ti–C bond in the cyclopropane forming step. The results have been interpreted in the framework of ate complex mechanism, suggesting formation of pentacoordinated titanium ate species as a prerequisite of high enantiocontrol.
Keywords: titanium; Kulinkovich reaction; cyclopropanation; esters; cyclopropanols; asymmetric synthesis; reaction mechanisms